(untitled) (Journal of Dhaka Medical College, 2017)
One of the common reasons of primary hyperparathyroidism is parathyroid adenoma. This can present in different ways- diffuse bone pain, multiple stones in the body warranting repeated surgery, renal failure, abdominal discomfort, depressed mood etc. Here we present a young women presented with surgical removal of gall stone and renal stones, pathological fractures and her generalized bodyache was treated for rheumatological cause for a long time. After surgical removal of adenoma he got back to life within couple of months. J Dhaka Medical College, Vol. 26, No.1, April, 2017, Page 83-85